2017
DOI: 10.1021/acs.inorgchem.6b02673
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Borane Dehydrogenation Catalyzed by (κ4-EP3)Co(H) [EP3 = E(CH2CH2PPh2)3; E = N, P] and H2 Evolution from Their Interaction with NH Acids

Abstract: Two Co(I) hydrides containing the tripodal polyphosphine ligand EP, (κ-EP)Co(H) [E(CHCHPPh); E = N (1), P (2)], have been exploited as ammonia borane (NHBH, AB) dehydrogenation catalysts in THF solution at T = 55 °C. The reaction has been analyzed experimentally through multinuclear (B, P{H}, H) NMR and IR spectroscopy, kinetic rate measurements, and kinetic isotope effect (KIE) determination with deuterated AB isotopologues. Both complexes are active in AB dehydrogenation, albeit with different rates and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 83 publications
1
32
0
Order By: Relevance
“…Waterman and co‐workers reported that cyclopentadienylcobalt complexes Cp R Co(CO) 2 I (R=H, Me; Figure ) catalyze ammonia borane (AB) dehydrogenation at elevated temperatures (65 °C) . The authors performed catalytic transfer hydrogenations with styrenes, alkynes, and olefins with an excess (8 equiv) of AB at 65 °C within 6 h. Tripodal polyphosphine cobalt(I) hydrides (Figure ), recently reported by Shubina and co‐workers, exhibited similar activity in the AB dehydrogenation . A mechanism was proposed based on DFT calculations.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Waterman and co‐workers reported that cyclopentadienylcobalt complexes Cp R Co(CO) 2 I (R=H, Me; Figure ) catalyze ammonia borane (AB) dehydrogenation at elevated temperatures (65 °C) . The authors performed catalytic transfer hydrogenations with styrenes, alkynes, and olefins with an excess (8 equiv) of AB at 65 °C within 6 h. Tripodal polyphosphine cobalt(I) hydrides (Figure ), recently reported by Shubina and co‐workers, exhibited similar activity in the AB dehydrogenation . A mechanism was proposed based on DFT calculations.…”
Section: Introductionmentioning
confidence: 90%
“…Various dehydrogenation and transfer hydrogenation protocols have been developed with precious metal catalysts, and the underlying mechanisms have been thoroughly studied . By contrast, dehydrogenations are far less advanced with the abundant and cheaper late 3d metals, despite the recent progress with Ti, Mn, Fe, Co, and Ni catalysts …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schneider has compared the pre‐catalysts RuH(PMe 3 ){N((CH 2 ) 2 P i Pr 2 ) 2 } and RuH 2 (PMe 3 ){NR((CH 2 ) 2 P i Pr 2 ) 2 } (R=H, Me) in the dehydropolymerization of H 3 B⋅NH 3 , wherein subtle changes in catalyst structure resulted in mechanistic changes based on experimental and computational findings . Dehydrogenation of ammonia‐borane by the cobalt catalysts CoH{E(CH 2 CH 2 PPh 2 ) 3 } produces (H 2 BNH 2 ) n when E=P, but when E=N two equivalents of H 2 are liberated and B‐(cyclotriborazanyl)amine–borane (BCTB), borazine, and polyborazylenes are obtained, which was attributed to the coordinative flexibility of the NP 3 ligand . Further understanding of how catalyst structure influences mechanism will be essential for understanding and optimization of reactivity for the tailored production of polymeric materials.…”
Section: Catalystsmentioning
confidence: 99%
“…As such, the mechanism does not involve an anchoring M−N (or M−B) bond for chain propagation, and it is also proposed that H 2 does not act to modify the polymer chain length. An unusual mechanistic pathway calculated by Rossin and Shubina involves B−N cleavage chain‐growth, in which BH 3 and NH 3 moieties are added individually at a cobalt tetraphosphine center …”
Section: Mechanismmentioning
confidence: 99%